Potential role for furosemide in the treatment of acute respiratory distress syndrome (ARDS) and an unusual presentation of pulmonary embolism in a complex patient. Issue 8 (24th August 2020) - Zornitzki, Lior; Bornstein, Gil
Abstract : An 81-year-old woman was admitted to our hospital after experiencing syncope. She was diagnosed with a large pulmonary embolism and was hemodynamically unstable therefore requiring endotracheal intubation and norepinephrine support. She presented with an upper gastrointestinal bleed which prevented her from receiving tissue plasminogen activator. She was treated with enoxaparin and ceftriaxone. Her blood, sputum and urine cultures were negative. When transferred to our ward, her antibiotic treatment was changed to piperacillin–tazobactam. A lumbar puncture was not suggestive of a central nervous system infection. Chest X-rays demonstrated rapid advancement of diffuse bilateral infiltrates which were not present at first and were interpreted by radiology consultation as suggestive of acute respiratory distress syndrome. An echocardiography showed right ventricle dilatation without left-sided heart failure. Diuretics were added and with this treatment, a quick respiratory improvement was noted as she regained consciousness and extubated shortly after.